THE EFFECT OF RECEIVABLES TURNOVER EFFECTIVENESS ON ECONOMIC RENTABILITY IN PT. YAMAHA FINANCE IN JAKARTA, INDONESIA - Oliver Hasan Padmanegara; Deni Irwansyah; Dede Kasmadi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study aims to determine the effect of Receivables Turnover Effectiveness on Economic Profitability at PT. Yamaha Finance in Jakarta. The method used is explanatory research. The analysis technique uses statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study the Effectiveness of Accounts Receivable Turnover variables obtained an average value of 45.34%. The Economic Rentability variable obtained an average value of 44.22%. The Effectiveness of Receivable Turnover has a positive and significant effect on Economic Profitability with a regression equation value of Y = 23,600 + 1,496X, and a correlation coefficient of 0.750 or has a strong relationship with a determination value of 56.3%. Hypothesis testing obtained significance 0,000 <0.05.